Evaluation of the effects of fatty ester isomerization and turpentine-derived additive introduction on biodiesel cold flow properties and oxidation stability - Antonius Indarto; Yano Surya Pradana; Alif Kembara Alam; I Gusti Bagus Ngurah Makertihartha; Tirto Prakoso; Tatang Hernas Soerawidjaja (International Journal of Renewable Energy Development, 2026)
Biodiesel is a cleaner and renewable combustion fuel that globally serves as an effective alternative to fossil diesel. The current application of this biofuel is still restricted to specific concentration due to its poor cold flow properties (CFPs) and low oxidation stability (OS). Later, isomerization process was offered to improve cold flow properties as well as oxidation stability. In this study, palm-biodiesel isomerization was carried out atmospherically using SO4/SnO2 catalyst, prepared via wet nitration method, in the stirred batch reactor at temperature of 200oC, catalyst loading of 10 wt%, stirring speed of 900 rpm, and under N2 flow. The performance of catalyst and the effect of fatty ester isomerization on CFPs and OS were investigated. For comparative study, the effect of bio-additive (turpentine oil and α-terpineol) introduction, at concentrations of 1−10 vol%, on CFPs and OS was also evaluated. The isomerization results demonstrated a conversion ratio of 12.54±0.60%, an isomerization selectivity of 75.92±5.79%, and an overall turnover frequency of 1.75×10−1±8.5×10−3 h−1. This reaction had a small reduction in pour point (ΔPP = ‒1oC), a minor elevation in cloud point (ΔCP = 0.50±0.15oC), and a slight improving effect in OS (ΔOS = 1.36 h). Furthermore, the optimum insertion of bio-additive was α-terpineol at concentration of 5 vol%, demonstrating a more significant enhancement in CFP parameters (ΔPP = ‒1oC; ΔCP = ‒1.75±0.15oC). Nevertheless, it significantly reduced OS level (ΔOS = ‒11 h), although the absolute value (OS = 10.36 h) remains compliant with international standards.